Histopathologic Progression and Metastatic Relapse Outcomes in Small Cell Neuroendocrine Carcinomas of the Urinary Tract - Mohammad Jad Moussa; Georges C. Tabet; Arlene O. Siefker‐Radtke; Lianchun Xiao; Nathaniel R. Wilson; Jianjun Gao; Christopher J. Logothetis; Petros Grivas; Byron Lee; Amishi Y. Shah; Pavlos Msaouel; Roger Li; et al. (Cancer Medicine)
ABSTRACT Introduction Small cell neuroendocrine carcinoma of the urinary tract (SCNEC‐URO) has an inferior prognosis compared to conventional urothelial carcinoma (UC). Here, we evaluate the predictors and patterns of relapse after surgery. Materials and Methods We identified a definitive‐surgery cohort (n = 224) from an institutional database of patients with cT1‐T4NxM0 SCNEC‐URO treated in 1985–2021. Histopathologic review was conducted by independent pathologists. Relapse event was the time‐to‐event outcome, and relapse probabilities were estimated using a competing risk method with cumulative incidence functions (CIFs). Fine‐Gray distribution models assessed covariate associations. Results Most patients (161, 71.9%) received neoadjuvant chemotherapy (neoCTX). Ninety two (41%) patients had relapse with 77 (83.7%) having distant organs as first metastatic sites, including 10 (10.9%) with exclusive central nervous system (CNS) metastases, mostly (9/10) within 1 year of surgery. Patients with pathologic complete response (pCR) after neoCTx had the lowest 5‐year CIF (16.5% [95% CI 9.3%–25.6%]). Patients with remaining exclusively small cell (SC) histology had the highest CIF (85.7% [95% CI 46.6–96.9]). Patients with eradicated SCNEC but remaining UC components had an intermediate‐risk CIF (32.5% [95% CI 18.6–47.2]). Multivariable analysis adjusting for neoCTx, clinical stage at diagnosis (T3/4, N0/N+ vs. T1/T2, N0), and pathologic stage (pN+ vs. pN0) demonstrated that any SCNEC histology at resection (vs. pCR) was associated with relapse risk (hazard ratio = 3.69 [95% CI 1.91–7.13], p = 0.0001). Conclusions SCNEC‐URO is a systemic disease with high risk of distant relapse including CNS. Our findings highlight unmet needs for neoadjuvant/adjuvant approaches targeting the rare SCNEC subtype and suggest adding CNS surveillance within the first year after definitive surgery to high‐risk patients. Précis (Condensed Abstract) Alongside neoadjuvant chemotherapy and cancer stage, histology at resection strongly impacts relapse risk in small cell neuroendocrine carcinomas of the urinary tract. The incidence of brain metastasis is notably higher than in “traditional” urothelial cancer within the first year after surgery, especially if small cell cancer persists, thus necessitating close neurological monitoring during this period.